Moral distress in nursing personnel Sufrimiento moral en trabajadores de enfermería Sofrimento moral em trabalhadores de enfermagem - Edison Luiz Devos Barlem; Valéria Lerch Lunardi; Guilherme Lerch Lunardi; Jamila Geri Tomaschewski-Barlem; Rosemary Silva da Silveira; Graziele de Lima Dalmolin (Universidade de São Paulo, 2013)
OBJECTIVE: to analyze the frequency and intensity of moral distress experienced by nursing personnel in southern Brazil, covering elements of their professional practice. METHOD: a survey was undertaken in two hospitals in Rio Grande do Sul, Brazil, with 247 nurses. Data was collected by means of the adapted Moral Distress Scale. RESULTS: the perception of situations that lead to moral distress is enhanced in nurses and in nursing staff working in institutions with greater openness to dialogue, which hold team meetings, with fewer working hours and a greater ratio of professionals to patients. CONCLUSION: understanding moral distress allows us to go beyond solving the problems of the workers themselves, enabling the development of an ethics of active individuals and wide opportunities, defined mainly by the relationship with oneself. OBJETIVO: analizar la frecuencia e intensidad del sufrimiento moral vivido por los profesionales de enfermería del sur de Brasil, abarcando los elementos de su rutina profesional. MÉTODO: investigación survey en dos hospitales, con 247 profesionales de enfermería. Los datos fueron recolectados mediante aplicación de la adaptación del Moral Distress Scale. RESULTADOS: la percepción de situaciones que conducen al sufrimiento moral es intensificada en enfermeros; en trabajadores de enfermería que actúan en instituciones con mayor apertura al dialogo, que realizan reuniones de equipo, con menos horas de trabajo y mayor relación del número de profesionales por paciente. CONCLUSIÓN: entender el sufrimiento moral permite ir más allá de la resolución de los problemas de los propios trabajadores, lo que posibilita la elaboración de una ética de sujetos activos y de amplias posibilidades, definidas principalmente por la relación consigo mismo. OBJETIVO: analisar a frequência e a intensidade de sofrimento moral vivenciado por trabalhadores de enfermagem do Sul do Brasil, contemplando elementos do seu cotidiano profissional. MÉTODO: survey realizado em dois hospitais do Rio Grande do Sul, Brasil, com 247 profissionais de enfermagem. A coleta dos dados ocorreu mediante aplicação da adaptação do Moral Distress Scale. RESULTADOS: a percepção de situações que conduzem ao sofrimento moral é intensificada em enfermeiros e em trabalhadores de enfermagem que atuam em instituições com maior abertura ao diálogo, realizam reuniões de equipe e têm menores jornadas de trabalho. Essa percepção também é intensificada quando se observa maior relação no número de profissionais por pacientes. CONCLUSÃO: compreender o sofrimento moral permite ir além da resolução dos problemas dos próprios trabalhadores, possibilitando a elaboração de uma ética de sujeitos ativos e de amplas possibilidades, definidas principalmente pelas relações consigo mesmos.